Madagascar, 29 mars 1947, « Tabataba ou parole des temps troubles » - Valérie MAGDELAINE-ANDRIANJAFITRIMO (E-REA)
The rising of 1947, when Malagasy rebels stood against French settlers, and the brutal repression which followed, have been neglected and denied in both colonial memory and Malagasy discourse. Historians still offer conflicting analyses of the insurrection. These fluctuating memories reveal to what extent the postcolonial present is still haunted by the colonial past. Significantly, the events of 1947 are rarely represented in Malagasy literature. Writer Jean-Luc Raharimanana is a rare exception. Indeed he has devoted quite a few of his works—a short story, a novel, an essay, and a play—to the topic, which he has used to reflect on the concept of the notion of “mutidirectional memory”, first elaborated by Michael Rothberg. And in fact, history seems to have caught up with Raharimanana’s work. His play was to have been performed in the Indian Ocean in 2008, but the tour was suspended, raising suspicions of censorship by the French government. The various interpretations which have been provided for this supension may well be the best answer to the rumor or, « tabataba ». This is the name which was given to the 1947 events and it is regarded as a form of discursive resistance on the part of the Malagasies.